Catalisadores magnéticos à base de ferritas de Co ou Zn e de heteroestruturas TiO2/Ferrita – Avaliação na degradação fotocatalítica de lignina - Souza, Bruna Gonçalves de (Universidade Federal de São Carlos, 2018)
Vinasse derived from beverage industry represents a serious environmental risk if not properly treated, mainly attributable to the presence of organic macromolecules with complex structure and composition, the recalcitrant compounds, which gives undesirable properties like high chemical oxygen demand (COD) and an increase of toxicity. Lignin, mainly responsible for the dark coloration characteristic of vinasse, is a compound of difficult degradation, which has not been well explored so far due to the difficulty in developing a viable method able to dealing with the extremely low bioavailability of this molecule, especially due to its recalcitrant characteristics. Among the treatment options, photocatalysis has been outstanding due to the production of extremely reactive radicals which may conduct to complete degradation or to an increase of biodegradability of these compounds in biological process. On the other hand, the catalyst recovery, usually TiO2 nanoparticles, might represent a limitation of photocatalysis. In this regard, ferrites have been used to the formation of TiO2 heterostructures, in order to attain magnetic properties that allow the catalyst recovery from the effluent by the application of an external magnetic field. Furthermore, the ferrites, at the presence of TiO2 and UV radiation, provides the iron source for the photo-Fenton reaction, which contributes to the production of extremely oxidative radicals. In this context, the objective of this project was to synthetize, by the means of microwave-assisted hydrothermal method, magnetic ferrites, pure or doped with Co or Zn, in addition of TiO2 heterostructures, aiming the photocatalytic degradation of lignin. The Rietveld refinement of the XRD results evidenced the formation of spinel-like structures at the pure or doped ferrites. The formation of the TiO2/ferrite heterostructure was verified through HRTEM images, and these samples showed higher SBET in comparison to pure P25 titania. The DRS-UV-Vis analyses indicated that the heterostructures absorption bands were extended to the visible light domain. All the photocatalysts exhibited magnetic properties. The maximum lignin degradation for the H5Zn95Ti heterostructure occurred at pH = 2 and 500 ppm of H2O2.
Keywords: Lignina; Fotocatálise; Ferrita; Foto-Fenton; Heteroestrutura; Lignin; Photocatalysis; Ferrite; Photo-Fenton; Heterostructure; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA